Between Worlds Understanding Ritual Cave Use in Later Prehistory - Büster, Lindsey; Warmenbol, Eugène; Mlekuž, Dimitrij; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The recent resurgence of academic interest in caves has demonstrated the central roles they played as arenas for ritual, ceremony and performance, and their importance within later prehistoric cosmologies. Caves represent very particular types of archaeological site and require novel approaches to their recording, interpretation and presentation. This is especially true in understanding the ritual use of caves, when the less tangible aspects of these environments would have been fundamental to the practices taking place within them. Between Worlds explores new theoretical frameworks that examine the agency of these enduring 'natural' places and the complex interplay between environment, taphonomy and human activity. It also showcases the application of innovative technologies, such as 3D laser-scanning and acoustic modelling, which provide new and exciting ways of capturing the experiential qualities of these enigmatic sites. Together, these developments offer more nuanced understandings of the role of caves in prehistoric ritual, and allow for more effective communication, management and presentation of cave archaeology to a wide range of audiences.
Between Worlds: Bridging the Divide between Method and Theory in Understanding the Ritual Use of Caves in Prehistory -- Part I: Theoretical Frameworks for Caves as Dynamic Spaces -- Caves as Vibrant Places: A Theoretical Manifesto -- Do Caves Have Agency? -- Animate Caves and Folded Landscapes -- Familiar Caves and Unfamiliar Landscapes: Approaching Cave-Use During the 1st Millennia in Britain -- How to Detect Ritual in Middle Bronze Age Central Italy? A Contextual Approach at Pastena Cave -- Pan Rituals of Ancient Greece Revisited -- The Watery Way to the World of the Dead: Underwater Excavations (Old and New) at the Cave of Han-sur-Lesse, Belgium -- Part II: Innovative Digital Capture Techniques in Cave Archaeology -- The Bronze Age Decorated Cave of Les Fraux: Ritual Uses of an Atypical French Heritage Site -- From Macro to Micro: Multi-scalar Digital Approaches at the Sculptor's Cave, NE Scotland -- How a Community Digital Heritage Project has Helped to Imagine the Circumstances of Pictish symbols in the Wemyss Caves, Scotland -- Reverberant Spaces Preferentially Selected by Prehistoric Artists: Ritualistic Use of Sound Underscored by Choice of Subject Matter.
Keywords: Archaeology; Archaeology